PENGARUH PRODUKTIVITAS TENAGA KERJA TERHADAP PROYEK PEMBANGUNAN GEDUNG RUANG KELAS BARU (RKB) MADRASAH IBTIDAIYAH NEGERI 5 MALUKU TENGAH - Nahumarury, Aulia; Serang, Rudy; Abdin, Maslan (Journal Agregate, 2024)
Construction  projects are one of the of the activities where the results of the work are influenced by the productivity of the workforce. Activities in construction projects are interrelated, so that if one activity is late it will hinder other activities in the field. Likewis, construction activities are complex work and require more attention in their implementation. The aim of  this research is to obtain what factors influence labor productivity and determine the presentation of the influence of independent variables on labor productivity in the classroom building (RKB) construction project of madrasah ibtidaiyah negeri 5 maluku tengah. The analysis method used in the research this is with the help of the SPSS version 26 program. In the  new classroom building (RKB) Construction project of madrasah ibtidaiyah negeri 5 maluku tengah there are several factor that influence labor productivity including labor, material, weather and environmental factors and the presentation of the influence of independent variables on labor productivity, which is 88.1% and the remaining 11.9% was influenced by other variables not tested in this study.